What Do Freshmen Want? Career Path Preferences Among Students - Ivana Milinković; Ivana Kovačević; Dobrivoje Mihailović (Management, 2017)
This study assessed the possible relation between life goal aspiration/orientation, department affiliation, gender and career path preferences. For this study we used data from 364 freshmen from the Faculty of Organizational Sciences (FOS), University of Belgrade, with the intention to find out what their aspirations and career plans are. Studying at the FOS gives them opportunity to become entrepreneurs, as well as managers, so we wanted to examine whether their general life aspirations are related to their desired career plans. While results indicate that there is no substantial link between career preferences and life aspirations in this specific point of their life, we found that gender and department of study may have some impact on the career preferences. JEL Classification: I23, C80, C83, L26